Investigating actual and accrual earnings management in companies - Zadeh, Siamak Hajjari (International Journal of Psychosocial Rehabilitation, 2020)
This research examines the relationship between accounting conservatism and earning management. The research population includes the companies listed in Tehran Stock Exchange whose periods are from the beginning of 2010 to the end of 2018. For this purpose, we selected 65 companies as the sample. 19 companies are of political connection and 46 companies are without no political connection. Multiple linear regression models and t-test were used to investigate the research hypotheses. The results show that there is a negative and significant relationship between conservatism and earning management in companies without political connections and companies with political connections. The conservatism in companies with political connections is low compared to other companies and statistically significant. The results also show that the amount of earning management used in companies with political connections is high compared to other companies and statistically significant. There is also no significant difference in earning management and conservatism in politically non-connected and dependent companies.